2015
DOI: 10.58897/injns.v28i2.235
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adolescents' Family Meal Eating Patterns upon their Weight Control Behaviors at Secondary Schools in Baghdad City

Abstract: Objective: The study aimed to identify the adolescents' family meal eating patterns, and find out the relationship between adolescents' family meal eating patterns and their weight control behaviors. Methodology: A descriptive study was conducted on impact of adolescents' family meal eating patterns upon their weight control behaviors in secondary schools at Baghdad city, starting from 20th of April 2013 to the end of October 2014. Non- probability (purposive) sample of 1254 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…More than one-third of the pupils demonstrated satisfactory achievement, according to the teachers' reports of the kids' performance. also demonstrates the insufficient monthly household income (11) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than one-third of the pupils demonstrated satisfactory achievement, according to the teachers' reports of the kids' performance. also demonstrates the insufficient monthly household income (11) .…”
Section: Discussionmentioning
confidence: 99%
“…The age group enrolled in this study (Table 1) lies in the adolescent period (11)(12)(13)(14)(15)(16)(17)(18)(19) years. The present study revealed a higher prevalence of anemia among the studied females at the age of 17-18 years (43.5%).…”
Section: Discussionmentioning
confidence: 99%